Social capital and access to credit in post-conflict Lira, northern Uganda. Issue 4 (8th August 2017) - Malual, Joseph D.; Mazur, Robert E.
Abstract: This study builds on research about the importance of informal saving associations and social relations to understand the strategies employed by households in post-conflict situations to access financial capital. The study examines the impact of social capital on accessing loans among formerly displaced households in Lira district. The contributions of sociodemographic and socioeconomic factors for access to loans were investigated. Data were collected from March–July 2011 through interviews with 221 household heads and through field research observations. Consistent with our hypotheses, social capital was strongly associated with loan access. Multiple regression analyses revealed the influence of age, gender, and educational level of household heads, as well as the impact of land and livestock ownership, on accessing loans. Results of this study can inform the design of development programs that effectively address challenges associated with access to financial capital and promote sustainable livelihoods in post-conflict settings.